The application of repertory grid analysis in eliciting conceptual frameworks and classificatory knowledge of biological natural kinds concepts - McCloughlin, Thomas John Johnston (Trinity College (Dublin, Ireland). School of Education, 2008)
Concepts give structure and order to the world around us. However, many learners are impeded by the perceived difficulty of concepts presented to them, and as a result of the mode of presentation. Students' conceptual structures have been studied at length in science education in the hope of remediating impediments to learning. Despite much research in conceptual development, and prior conceptions in particular, relatively little has focused on the structures of biological concepts and less again on biological concepts that are natural kinds. This work describes four empirical studies concerning biological natural kind concepts that involve using repertory grid analysis (RGA) as a tool for investigating the structures of representations of these concepts and how students classify them. RGA possesses a powerful set of tools, which a researcher may utilise in order to examine the structures of conceptual frameworks, as concept mapping also claims to do. Modem RGA is computer-based tool and models of conceptual structures can be represented in graphical form. Protocols were used to compare the conceptual frameworks of a group of individuals, and conceptual change can be monitored in a rigorous way that is not possible with customary concept mapping techniques. Convenience samples of senior primary and post-primary students were used in the Republic of Ireland, Northern Ireland and Valencia; two qualified biologists were retained to provide a base-line comparison. The studies consisted of tasks whereby students were presented with sets of stimuli (the first study which used words, and the others used graphics): (i) one set of five equids and the concept 'goat'; (ii) two sets of six equids (consisting of examples drawn from the following three categories: extant, extinct and imaginary); (iii) a large set of mammals; and (iv) five sets of dicotyledonous plant families.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin